The Influence of Work Discipline and Work Environment on Employee Work Productivity at the Mona Plaza Hotel Pekanbaru - Wira Safitri; Seno Andri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of work dicipline and employee work environment at the Mona Plaza Hotel Pekanbaru. The research method used is quantitative. The sample for this research was 32 employees with data collection techniques using questionnaires. The data obtained was analyzed through linear regression analysis with the SPSS program. The research results show; (1) There is a significant influence of work discipline on employee work productivity at the Mona Plaza Hotel Pekanbaru. The obtained tcount value > ttable or 8.361 > 1,697 with a significance of 0,000 < 0,05. The results of simple linear regression analysis show that if work discipline increases by 0,403, it will increase the work productivity of Mona Plaza Hotel Pekanbaru employees by 7,211 constantly. (2) There is a significant influence of the work environment on employee work productivity at Mona Plaza Hotel Pekanbaru. The work environment variable has a calculated tcount value > ttable or 6,873 > 1,697 with a significance of 0,000 < 0,05. The results of simple linear regression analysis show that if the work environment increases by 0,757, it will increase employee productivity at Mona Plaza Hotel Pekanbaru by 5,085 constantly. (3) There is an influence of work discipline and work environment on employee work productivity at the Mona Plaza Hotel Pekanbaru. From the results of the F test, it is known that the value of Fcount > Ftable is 42,988 > 3,32 with a significance value of 0,000 < 0,05.